2017
DOI: 10.14740/wjon1031w
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Smooth Muscle Tumor of Uncertain Malignant Potential: Clinicopathologic-Sonographic Characteristics, Follow-Up and Recurrence

Abstract: BackgroundUterine smooth muscle tumor of uncertain malignant potential (STUMP) is rare tumor, and regarded as sub-classification in uterine smooth muscle tumors between benign and malignant criteria. In this study, we evaluated characteristics of cases with STUMP diagnosis in a 10-year period.MethodsWe retrospectively evaluated medical records of patients with histopathological STUMP diagnosis in Istanbul Training and Research Hospital, a tertiary center. We analyzed preoperative demographic, clinical features… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 10 publications
2
29
0
5
Order By: Relevance
“…According to the limited statistics, STUMP is generally found in younger aged women than other tumors of the uterus. In this study, the median age of patients was 42 years, similar to previously reported cases (6)(7)(8)(9)(10)(11)(12). Since the patients are young, preserving fertility is an essential consideration in the selection of treatment.…”
Section: Discussionsupporting
confidence: 83%
“…According to the limited statistics, STUMP is generally found in younger aged women than other tumors of the uterus. In this study, the median age of patients was 42 years, similar to previously reported cases (6)(7)(8)(9)(10)(11)(12). Since the patients are young, preserving fertility is an essential consideration in the selection of treatment.…”
Section: Discussionsupporting
confidence: 83%
“…STUMP is diagnosed more often in premenopause, at an average age of 44 years. As seen in our cohort of patients, the most frequent chief complaint, leading to surgery and postoperative diagnosis of STUMP, is heavy menstrual bleeding with or without development of anaemia [5]. The clinical presentation of STUMP does not differ from other SMTs such as leiomyoma or leiomyosarcoma -pelvic pain, pelvic mass, abnormal uterine bleeding, compression of adjacent organs and secondary anaemia, infertility, dysmenorrhoea, and abnormal vaginal discharge may all be present [6][7][8][9][10], thus rendering non-specific symptoms in all these histologically and clinically different conditions.…”
Section: Discussionmentioning
confidence: 58%
“…Therefore, it is hard to predict the biological behavior, metastatic potential, or prognosis of STUMP. Reported survival outcome is good, with a five-year survival rate of 92-100% (15). In summary, we described a rare manifestation of DPL with atypical features and comorbid uterine STUMP, stable at the 20-month follow-up after the surgery.…”
Section: Discussionmentioning
confidence: 74%